1982
DOI: 10.1182/blood.v60.1.59.59
|View full text |Cite
|
Sign up to set email alerts
|

Radioimmunoassay of factor V in human plasma and platelets

Abstract: Homogeneous, single-chain human factor V was used to develop a double antibody competition radioimmunoassay to measure factor V concentrations in plasma and platelets. Standard curves were constructed that allow for the detection of as little as 20 ng factor V/ml of plasma. Normal factor V concentrations range from 4 to 14 micrograms/ml of plasma with an average value of 7.0 +/- 2.0 micrograms/ml (n = 64). No correlation was observed between antigen levels and age or sex. The radioimmunoassay data are consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
110
0
1

Year Published

1985
1985
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(113 citation statements)
references
References 0 publications
2
110
0
1
Order By: Relevance
“…1b) or thrombin-activated releasate (Fig. 2b) is approximately 60% of the normal control, indicating that her platelets should contain from 2700 to 9000 molecules of FV/platelet [4]. Therefore, under the conditions of the study shown in Fig.…”
Section: Discussionmentioning
confidence: 81%
“…1b) or thrombin-activated releasate (Fig. 2b) is approximately 60% of the normal control, indicating that her platelets should contain from 2700 to 9000 molecules of FV/platelet [4]. Therefore, under the conditions of the study shown in Fig.…”
Section: Discussionmentioning
confidence: 81%
“…*P < .01; † P < .001; ‡ P < 0.0001 approximately 5-to 10-fold, which is consistent with previous studies. 45,46 In platelets, an even larger concentration range was observed, at approximately 10-fold for TFPI, and approximately 20-fold for fV and PS. This suggests that the effect of race on the concentration of these proteins is minor relative to random variation.…”
Section: Discussionmentioning
confidence: 98%
“…About 18%-25% of FV is also stored in platelet alpha-granules so platelet transfusions can effectively treat bleeds in FV deficiency, as they were given in the acute treatment of our patient's initial intracranial hemorrhage. 2,9 Platelet transfusions may actually be superior to FFP because platelets localize at the site of vascular injury and release FV from alpha-granules, which persists in circulation well after FV from FFP becomes undetectable. 10 In fact, the reason bleeding tendency in FV deficiency does not correlate well with actual factor levels may be because of compensation by platelet FV.…”
Section: Discussionmentioning
confidence: 99%